1999
DOI: 10.1177/074873099129000399
|View full text |Cite
|
Sign up to set email alerts
|

Novel Effects on the Gonyaulax Circadian System Produced by the Protein Kinase Inhibitor Staurosporine

Abstract: The protein kinase inhibitor staurosporine was found to cause a dramatic increase in the free-running period (FRP) of circadian rhythms in the dinoflagellate Gonyaulax polyedra, and its effect was similar when added at different phases of the circadian cycle. Chronic exposure to staurosporine lengthened the FRP by as much as 7 h without significantly affecting the amplitude or waveform of the bioluminescence rhythm. The effect on the length of the FRP occurred only above a threshold concentration, and it laste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In similar studies, Price and coworkers have shown that two alleles of Drosophila dbt (dbt S and dbt L ) change the period of the clock presumably by affecting the degradation of PER (26,27). Similarly, in the dinoflagellate Gonyaulax polyedra, various protein kinase inhibitors have been shown to affect circadian rhythmicity (35,41). Interestingly, the same kinase inhibitor we have used, 6-DMAP, has been shown to have a period-lengthening effect, suggesting phosphorylation also plays a role in the Gonyaulax clock.…”
Section: Discussionmentioning
confidence: 92%
“…In similar studies, Price and coworkers have shown that two alleles of Drosophila dbt (dbt S and dbt L ) change the period of the clock presumably by affecting the degradation of PER (26,27). Similarly, in the dinoflagellate Gonyaulax polyedra, various protein kinase inhibitors have been shown to affect circadian rhythmicity (35,41). Interestingly, the same kinase inhibitor we have used, 6-DMAP, has been shown to have a period-lengthening effect, suggesting phosphorylation also plays a role in the Gonyaulax clock.…”
Section: Discussionmentioning
confidence: 92%
“…These proteins may serve important functions in pathways coupling the dinoflagellate clock to its hands. Protein phosphorylation plays an important role in the progress of the protein components that cycle in the core circadian clock (Dunlap 1999), and its role in the L. polyedrum clock is inferred from the effects of kinase and phosphatase inhibitors on the period and light‐dependent phase shifting of the bioluminescence rhythm (Comolli et al 1996, Comolli and Hastings 1999). In this study we also found by random sequencing of noncycling clones a gene (AF508265) encoding an ortholog of the Drosophila kinase “shaggy,” a clock‐protein that phosphorylates TIM and promotes nuclear translocation of the TIM/PER complex (Young and Kay 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Complementing the molecular genetic studies, experimental manipulation of kinases alters rhythms in diverse circadian systems (Eskin et al, 1984;Liu and Gillette, 1996;Krucher et al, 1997;Liu et al, 1997;Comolli and Hastings, 1999). Clock sensitivity to cGMPdependent pathways has emerged as a conserved feature of the nocturnal domain (Eskin et al, 1984;.…”
Section: Introductionmentioning
confidence: 99%